Busca ativa e apoio ao retorno e à permanência de jovens à/na escola no contexto (pós) pandêmico - Costa, Fernanda Luiza (Universidade Federal de São Carlos, 2024)
School dropout is a persistent issue in the Brazilian Elementary School System, particularly among adolescents and young people in public schools, escalated by the COVID-19 pandemic. The development of strategies to address this issue can contribute to public policies that promote school return and retention, as well as strengthen citizenship, social participation, and democratization in the country. This study is part of a broader ongoing project that actively seeks out young people who have faced difficulties completing their educational journeys in Elementary Schools across different Brazilian cities, aiming to keep them in school. A database was utilized regarding students who have dropped out or are at risk of dropping out, constructed in collaboration with public schools in São Carlos, SP, Brazil, and supplemented by other strategies to identify young people not included in these statistics. Based on this data, we contacted some young people to understand their reasons behind school dropout. This process involved establishing dialogical relationships to get closer to and grasp their individual and/or collective demands. Additionally, interviews were conducted with the young people, along with Individual and Territorial Follow-Up, a methodology from social occupational therapy, to identify the specific needs of each young person and create pathways for their return to school. The follow-up was carried out with three young individuals, aiming to understand the reasons for their school abandonment and to empower and support them in facing these challenges. One adolescent was supported for ten months and managed to return to the regular education system with the help of the Metuia-UFSCar team. However, after just over three months, she faced new difficulties in remaining in school and dropped out again. Two other young boys were supported for six months; one enrolled in the Youth and Adult Education System, while the other continues to face barriers in resuming their studies. Understanding the social, historical, economic, and political context in which contemporary youth are situated reveals contradictions surrounding social phenomena that lead to barriers preventing access to their rights, including education. Furthermore, current values and individualism in social relationships also hinder school retention. It is essential to ensure spaces that provide youth with reflections on the multiple intersections they experience, both individually and collectively, and to recognize the school’s potential in achieving this principle, despite existing fragilities. It is also crucial to discuss themes such as solidarity and respect, alongside what schools can intentionally do through collective interventions to prevent situations like school violence from being addressed in an individualized manner. The importance of discussing how schools operate and the strategies that are or can be implemented to address issues such as school violence, dropout, retention difficulties, learning challenges, and assessment formats is evident. Schools must, in a planned manner—especially through collective interventions—, create a more attractive, supportive, and respectful environment, not only facilitating the return of students but also ensuring their retention
Active search and support for the return and permanence of young people to/at school in the (post) pandemic context
Keywords: Juventudes; Educação; Evasão Escolar; Rede Social de Suporte; Comunidade; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL